POPULATION PARAMETERS OF GREY GORAL (Naemorhedus goral goral) AT TWO DIFFERENT SITES IN MACHIARA NATIONAL PARK, AZAD JAMMU AND KASHMIR, PAKISTAN - N. Ashraf; M. Anwar; I. Hussain; S. N. Mirza (Journal of Animal and Plant Sciences, 2015)
Grey goral (Naemorhedus goral goral) is a bovid mammal species, endemic to Asia; particularly occurs in southern slopes of the Himalayan mountains. This species is nearly threatened and their population is declining day by day due to illegal hunting and habitat loss. The population parameters of Grey goral were examined in Machiara National Park (MNP) by employing direct visual observations of animal, indirect signs such as pellet groups, and secondary information from wildlife staff and herders during 2012 - 2013. The mean population density of Grey goral in Machiara National Park was 2.66 individuals / km². The range of encounter rate (No./Scan) was 0.00 to 2.9. The population of Grey goral in Machiara site was higher (4.57/ km²) than Serli Sacha site (i.e., 0.76/km²). This might be that Grey goral preferred to use Machiara site due to less disturbance and avoided Serli Sacha site due to higher disturbance as a result of livestock grazing, fuel wood collection and other human related activities. A total of 30 goral herds were observed (Machiara=21, Serli Sacha= 9). The minimum herd size was two while maximum herd size was six. Mean herd size was 1.99 animals where larger groups were frequent in less disturbed areas (38%) in contrast to highly disturbed areas (12%). Number of fawns/female was highest during May (1.12) and June (0.71). Based on reported gestation period of Grey goral around six months, it could be concluded that their peak breeding season in MNP is November and December. Major threats to the survival of Grey goral in MNP are habitat degradation (fodder, fuel wood, medicinal herbs collection) and competition with livestock (over grazing). Future conservation efforts for Grey goral in MNP need to focus on protection and securing disturbance-free habitat.
Keywords: Population; Group size; Disturbance; Grey goral; Machiara National Park